2004
DOI: 10.1139/z04-096
|View full text |Cite
|
Sign up to set email alerts
|

Overwintering in the nest by hatchling map turtles (Graptemys geographica)

Abstract: We monitored 75 natural nests of Graptemys geographica (Lesueur, 1817) in central Pennsylvania to determine the tactics and patterns of hatchling emergence. Following incubation, all hatchlings in 95% of nests delayed emergence from their natal nest cavities throughout autumn and winter until the following spring. Nests were constructed in a variety of substrates ranging from loose sand or coal to hard-packed clay mixed with gravel. Time from egg deposition to natural hatchling emergence averaged 333 days. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 44 publications
(58 reference statements)
0
38
0
Order By: Relevance
“…Most (95 %) hatchling G. geographica overwinter in the nest in Pennsylvania (Nagle, Lutz & Pyle, 2004), where mortality is limited (5.4 %). Baker et al (2003) report similar data for hatchlings in northern Indiana, with 19 of 20 nests containing hatchlings that successfully overwintered (only one dead overwintering hatchling ; one nest had autumn emergence).…”
Section: Aquatic Turtles -Species Known or Suspected To Be Anoxiamentioning
confidence: 99%
“…Most (95 %) hatchling G. geographica overwinter in the nest in Pennsylvania (Nagle, Lutz & Pyle, 2004), where mortality is limited (5.4 %). Baker et al (2003) report similar data for hatchlings in northern Indiana, with 19 of 20 nests containing hatchlings that successfully overwintered (only one dead overwintering hatchling ; one nest had autumn emergence).…”
Section: Aquatic Turtles -Species Known or Suspected To Be Anoxiamentioning
confidence: 99%
“…In some species the majority of hatchlings remain in the nest until the following spring, although some fall emergence may occur. These include Painted Turtles (Chrysemys picta -Zwiefel 1989;Lindeman 1991;Pappas et al 2000), Common Map Turtles (Graptemys geographica -Pappas et al 2000;Baker et al 2003;Nagle et al 2004), and Diamondback Terrapins (Malaclemys terrapin; Baker et al 2006). For the two former species, it is assumed that if the hatchlings leave the nest, they overwinter aquatically, while for the latter species fall emergence coupled with aquatic or terrestrial overwintering has been reported (Draud et al 2004), as well as overwintering in the nest coupled with fall emergence (Baker et al 2006).…”
mentioning
confidence: 99%
“…Given that emergence date is likely a facultative response to environmental conditions (Gibbons and Nelson, 1978;Nagle et al, 2004), we expect emergence patterns to vary annually as well as geographically. There are only a few published accounts of the timing of emergence for western pond turtles, and most involve only a few nests.…”
Section: Discussionmentioning
confidence: 99%
“…In Mar., we installed enclosures inside the exclosures, which allowed us to determine the date of spring emergence (Nagle et al, 2004) and attach radio transmitters. By retaining hatchlings that could exit the larger-mesh exclosures, we were able to precisely determine the initial date of spring emergence and also allow us to attach transmitters.…”
Section: Methodsmentioning
confidence: 99%